1997
DOI: 10.1055/s-2007-1004318
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Early Postoperative Esophagoscopy for Occurrence of Benign Stenosis After Cervical Esophagogastrostomy

Abstract: Early postoperative esophagoscopy seems a safe and effective tool for the monitoring of the anastomosis healing after cervical esophagogastrostomy. The presence of extended mucosal ulcerations appeared as the most important factor in predicting BAS formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 0 publications
2
17
0
2
Order By: Relevance
“…Early postoperative esophagoscopy and dilatation have been reported by Trentino et al [27]and Orringer et al [28]. We do agree that dilatation of a leaking anastomosis may favorably influence healing because relative narrowing by local inflammation and spasm may contribute to obstruction distal to an esophageal leak and adversely affect spontaneous closure.…”
Section: Management Of Anastomotic Leakssupporting
confidence: 68%
See 1 more Smart Citation
“…Early postoperative esophagoscopy and dilatation have been reported by Trentino et al [27]and Orringer et al [28]. We do agree that dilatation of a leaking anastomosis may favorably influence healing because relative narrowing by local inflammation and spasm may contribute to obstruction distal to an esophageal leak and adversely affect spontaneous closure.…”
Section: Management Of Anastomotic Leakssupporting
confidence: 68%
“…between days 3 and 5 and dilatation when necessary, seems to result in a decreased need for multiple dilatation. Trentino et al [27]reported a 83% success rate after a mean of 3.6 dilatations when performing early endoscopy and dilatation. The presence of ulceration involving more than 50% of the anastomotic circumference is the most important factor in predicting development of anastomotic stricture [27].…”
Section: Stenosismentioning
confidence: 99%
“…Benigne Anastomosenstenosen nach Ösophagusresektion werden in der Literatur mit einer Häufigkeit von 9-56% angegeben [33,39,64,85].Anastomosenstenosen nach kolorektalen Resektionen werden mit einer Häufigkeit von 2-22% beschrieben [86,90]. Frühzeitig diagnostiziert kann durch eine effiziente endoskopische Therapie die Anastomosenstenose beseitigt und eine Reoperation vermieden werden.…”
Section: Sekundärkomplikationen Anastomosenstenosenunclassified
“…Although patients with early stage EC can benefit from surgery, complications drastically impair their quality of life and lead to increase in surgery-related mortality rates [5,6,7]. Dysphagia caused by anastomotic-stenosis is one of the major post-surgical complications occurring in 6.8-42% of patients after resection of esophageal cancer [8,9,10,11,12,13,14,15]. Thus, it is critical to define what is optimal treatment for this dreaded complication.…”
Section: Introductionmentioning
confidence: 99%